Associations of Modifiable Behavioral Risk Factor Combinations at 65 to 74 Years Old With Cognitive Health Span for 20 Years. Issue 7 (28th September 2022) - Smagula, Stephen F.; Biggs, Mary L.; Jacob, Mini E.; Rawlings, Andreea M.; Odden, Michelle C.; Arnold, Alice; Newman, Anne B.; Buysse, Daniel J.
ABSTRACT: Objective: Behavioral risk factors for dementia tend to co-occur and interrelate, especially poor diet, physical inactivity, sleep disturbances, and depression. Having multiple of these modifiable behavioral risk factors (MBRFs) may predict a particularly shortened cognitive health span and therefore may signal high-risk status/high intervention need. Methods: These secondary analyses of data from the Cardiovascular Health Study included 3149 participants aged 65 to 74 years (mean [standard deviation SD] age = 69.5 [2.5] years; 59.6% female). MBRF exposures were self-reports regarding a) diet, b) activity, c) sleep, and d) depression symptoms. We primarily analyzed MBRF counts. For up to 26 years of follow-up, we assessed the a) number of remaining cognitively healthy life-years (CHLYs) and b) percentage of remaining life-years (LYs) that were CHLYs (%CHLY). We estimated CHLYs as time before a dementia diagnosis, cognitive screener scores indicating impairment, proxy report indicating significant cognitive decline, or dementia medication use. Results: Participants averaged a remaining 16 LYs (SD = 7 LYs), 12.2 CHLYs (SD = 6.6 CHLYs), and 78.1% of LYs being CHLYs (SD = 25.6 CHLYs). Compared with having no MBRFs, having one was associated with 1 less LY and CHLY, but not a relatively lower %CHLY. In contrast, having 3+ MBRFs was associated with about 2 to 3 fewer LYs and CHLYs as well as about 6% lower %CHLY (95% confidence interval = −9.0 to −2.5 %CHLYs; p = .001). Conclusions: MBRF-related reductions in the cognitive health span are most apparent when people have multiple MBRFs. Future research is needed to determine if/how behavioral risks converge mechanistically and if dementia prevention efficacy improves when targeting MBRF combinations.